Gamified Android Learning to Foster Higher-Order Thinking in Students with ADHD - Susiaty, Utin Desy; Chandra Lesmana (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study addresses the problem of how the implementation of HOTS-based Android gamification influences the higher-order thinking skills of students with ADHD, a group that often faces challenges in traditional learning environments. A quantitative experimental research design was applied, involving 26 students with ADHD from four special needs schools (SLBs) in West Kalimantan. The intervention included HOTS-oriented Android gamified learning, and students' performance was measured using pre-tests and post-tests based on HOTS-level questions. The average pre-test score was 23.72, while the post-test score increased to 53.21. A paired sample t-test showed a significant improvement (t = 8.688 > t_table = 1.708, at a 5% significance level). However, only 57.69% of students met the minimum mastery criteria (KKM = 67), indicating that 15 out of 26 students achieved the expected learning standard. The implementation of HOTS-based Android gamification significantly improved the higher-order thinking skills of students with ADHD. Nonetheless, the overall results, based on average scores and classical completeness, indicate that many students still did not reach the expected level of mastery. Further enhancements in instructional design may be necessary to optimize outcomes for this group of learners.